On the nearly free simplicial line arrangements with up to 27 lines - Janasz, Marek (Analitic and Algebraic Geometry 4, 2022)
In the present note we provide a complete classification of nearly free (and not free simultaneously) simplicial arrangements of d ⩽ 27 lines.